Microbial dysbiosis and lack of SCFA production in a Spanish cohort of patients with multiple sclerosis - Moles, Laura; Delgado, Susana; Gorostidi-Aicua, Miriam; Sepúlveda, Lucía; Alberro, Ainhoa; Iparraguirre, Leire; Suárez, Jose Alberto; Romarate, Leire; Arruti, Maialen; Muñoz-Culla, Maider; Castillo-Triviño, Tamara; Otaegui, David; et al. (Frontiers in Immunology, 2022)
Background: Multiple Sclerosis (MS) is a chronic, demyelinating and immune mediated disease of the central nervous system caused by a combination of genetic, epigenetic and environmental factors. The incidence of MS has increased in the past several decades suggesting changes in the environmental risk factors. Much effort has been made in the description of the gut microbiota in MS, however little is known about dysbiosis on its function. The microbiota produces thousands of biologically active substances among which are notable the Short Chain Fatty Acids (SCFAs) excretion. Objectives: Analyze the interaction between Microbiota, SCFAs, diet and MS Methods: 16S, Diet questionaries’ and SCFAS quantification has been recovered from MS patients and controls. Results: Our results revealed an increment in the phylum Proteobacteria, especially the family Entero-bacteriaceae, a lack in total SCFAs excretion and an altered profile of SCFAs in a Spanish cohort of MS patients. These alterations are more evident in patients with higher disability. Conclusions: The abundance of Proteobacteria and acetate and the low excretion of total SCFAs, especially butyrate, are common characteristics of MS patients and, besides, both are associated with a worse prognosis of the disease.